Active Bodies, Confident Minds: Exploring the Relationship Between Physical Activity and Mathematics Self-Efficacy Among High School Students - Keano P. Ananayo; Frederick B. Chengay (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study examined the relationship between physical activity and mathematics self-efficacy among high school students. Specifically, it explored how engagement in physical activity influences students’ confidence in performing mathematics-related tasks. A descriptive–correlational research design was employed, involving 189 high school students from two selected schools in the Philippines. Data were collected using the Physical Activity Questionnaire for Adolescents (PAQ-A) and a Mathematics Self-Efficacy Scale. Descriptive statistics and Pearson Product–Moment Correlation were used for data analysis. Results revealed that students demonstrated a high level of physical activity (M = 4.21, SD = 0.61) and a high level of mathematics self-efficacy (M = 3.98, SD = 0.64). Furthermore, a high positive and statistically significant relationship (r = 0.76, p < 0.05) was found between physical activity and mathematics self-efficacy. These findings suggest that increased engagement in physical activity is associated with higher levels of confidence in mathematics. The study highlights the importance of promoting physical activity as part of a holistic educational approach that supports both physical and academic development. It underscores the role of schools in fostering environments that enhance students’ well-being and academic self-beliefs.